Carcinoma escamoso oral: análise retrospectiva de 185 casos - Monti, Lira Marcela [UNESP]; França, Diurianne Caroline Campos [UNESP]; Castro, Alvimar Lima de [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (My University, 2010)
The squamous cell carcinoma is the most common malignancy in the oral cavity, representing over 90% of cancers in this region. This study aimed to conduct an epidemiological study of oral squamous carcinoma cases diagnosed by the Department of Pathology, Department of Pathology and Clinical Propaedeutics in the Dentistry Faculty of Araçatuba - UNESP, in the period between 1995 and 2005. 185 cases were studied, it was observed that the oral floor and tongue were the sites most affected, with predominance in males, white race and aged between 41 and 60 years, noting that the majority of patients were smokers. Knowledge of these data is important for the dental surgeon to act preventively, contributing to early diagnosis of cancer.

O carcinoma escamoso é a neoplasia maligna orobucal mais comum, representando mais de 90% dos cânceres nessa região. Este trabalho objetivou realizar um estudo epidemiológico dos casos de carcinomas escamosos orais diagnosticados pelo Serviço de Patologia do Departamento de Patologia e Propedêutica Clínica da Faculdade de Odontologia de Araçatuba - UNESP, no período entre 1995 e 2005. Foram estudados 185 casos verificandose que o assoalho bucal e a língua foram os sítios mais afetados, com predomínio no sexo masculino e raça branca, e a faixa etária entre 41 e 60 anos, constatando-se que a maioria dos pacientes eram fumantes. O conhecimento desses dados é importante para que o cirurgião dentista possa atuar preventivamente, contribuindo para o diagnóstico precoce da neoplasia.
Oral squamous cell carcinoma: retrospective analysis of 185 cases
Keywords: Epidemiology; Epidemiologic measurements; Mouth neoplasms; Carcinoma; Squamous cell; Epidemiologia; Medidas em epidemiologia; Neoplasias bucais; Carcinoma de células escamosas